Plant-Based Solutions to Global Livestock Anthelmintic Resistance - French, Katherine E. (Ethnobiology Letters, 2018)
Anthelmintic resistance in livestock is increasing globally. Livestock intestinal parasites now develop resistance to synthetic anthelmintics within 2–10 years, collectively costing billions of dollars annually in lost revenue around the world. Over-reliance on commercial drugs and dips and changes in livestock management practices are key drivers of this trend. To date, current research has focused on identifying new anthelmintics from bacterial and fungal sources or even synthesizing new drugs that target parasite metabolism or reproduction. Plant-derived anthelmintics are a promising alternative, yet to date major research funders and scientists have overlooked this option. Until the mid-20th century, rural communities relied on plant-based methods of controlling livestock parasites. These methods include feeding livestock specific medicinal plants and trees, grazing livestock on herbal leys, and changing where livestock grazed based on ecological factors (e.g., flooding) that increased parasite burdens. Many historic texts and ethnological accounts record the ethnobotanical knowledge of rural communities and the plants they used to control livestock intestinal parasites. Some traditions persist today yet the farmers, graziers, and shepherds who hold this knowledge are rapidly disappearing and with them perhaps a potential long-term solution to anthelmintic resistance. This short perspective piece will cover recent research using ethnobotanical data as a means to identifying potential new anthelmintics; the morphological, physiological, and metabolic effect of plant secondary metabolites on parasites; and an overview of “best practices” which can reduce bias in assessments of plant bioactivity and increase reproducibility of test results. This will hopefully bring recent advances in ethnobiology, chemistry, and ecology to new audiences, and, potentially, spark new interest in using medicinal plants to improve livestock health.